Smooth solution of one boundary-value problem - Khoma, N. H.; Tsynalko, P. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study the boundary value problem for the quasilinear equation u u − uxx=F[u, ut], u(x, 0)= u(x, π)=0, u(x+w, t)=u(x, t), x ε ®, t ε [0, π], and establish conditions under which a theorem on the uniqueness of a smooth solution is true.